Hama Penggerek Batang Padi dan Teknologi Pengendalian - Baehaki S. E. (Iptek Tanaman Pangan, 2013)
Rice stem borer is an important pest on rice. Its occurrence and distribution needs to be monitored, for the purpose of its control measure. Recently a very high attack occurred on rice in the island of Java, especially in West Java and Central Java. The technological strategy for controlling borers is triangle action strategy, consisting the implementation of SOP borer control, building borer control unity in the community, and farming a strong national and local government commitment on borer control. The application of SOP for borer control, should base on the new economic threshold recently developed, namely based on pest monitoring using light traps, at 4 days after the first adult flight. Borer control should not based on the old economic threshold because by that time the damages had already occur, and sometimes the yield loss had been substantial.